2013
DOI: 10.1016/j.ntt.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance microscopy-based analyses of the neuroanatomical effects of gestational day 9 ethanol exposure in mice

Abstract: Animal model-based studies have shown that ethanol exposure during early gestation induces developmental stage-specific abnormalities of the face and brain. The exposure time-dependent variability in ethanol’s teratogenic outcomes is expected to contribute significantly to the wide spectrum of effects observed in humans with fetal alcohol spectrum disorder (FASD). The work presented here employs a mouse FASD model and magnetic resonance microscopy (MRM; high resolution magnetic resonance imaging) in studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
(56 reference statements)
2
38
0
Order By: Relevance
“…The cerebellum was 14% smaller with a significant change in shape, and bilaterally asymmetric, while the right and left cortices exhibited a trend towards slightly decreased volume. The cerebral cortex, hippocampus and right striatum were significantly distorted [159].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…The cerebellum was 14% smaller with a significant change in shape, and bilaterally asymmetric, while the right and left cortices exhibited a trend towards slightly decreased volume. The cerebral cortex, hippocampus and right striatum were significantly distorted [159].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Both of these processes have been confirmed in a number of PAE studies using a histological approach (for example [176]). Asymmetric alterations within a single brain structure, such as the cerebellum in the mice following GD9 exposure [159] and the cortical lobes in humans [5;17;27] were also reported. were not consistently observed in animals.…”
Section: Comparison Of Pae Effects In Humans and Animal Modelsmentioning
confidence: 99%
“…Seminal research by Sulik and colleagues has shown that a single acute dose of alcohol on each of these 3 days can produce distinct and profound craniofacial malformations that are reminiscent of sentinel clinical features of FAS (Parnell et al 2009, 2013; Godin et al 2010; Lipinski et al 2012). Sulik and colleagues used 2 doses of alcohol = 2.9 g/kg (4 h apart, i.p.)…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…Mouse models of early neurulation GD9–10 PAE show brain volume abnormalities compared with the controls but do not result in facial dysmorphologies (O’Leary-Moore et al 2010; Parnell et al 2013). In their MRI studies, Parnell and colleagues demonstrated that in contrast to GD7–8 PAE embryos, GD9–10 PAE embryos have no statistically significant reduction in crown–rump length or total body volume compared with their stage-matched controls (O’Leary-Moore et al 2010; Parnell et al 2013). GD9–10 PAE embryos also have a significant reduction in total brain volume of ~13.6% compared with the stage-matched controls (O’Leary-Moore et al 2010; Parnell et al 2013).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…Further, there is a preferentially selective and dose-dependent effect on the foetal dentate gyrus in response to pre-natal alcohol exposure, with changes exhibited in the density and/or number of dentate gyrus granule cells and with none of these alterations being observed when the exposure period does not include the third trimester-equivalent. In addition, rodent studies using other modalities, such as magnetic resonance imaging and behavioural testing, to evaluate the hippocampus have also found that change in volume may not be a sensitive indicator of pre-natal alcohol exposure, but that functional deficits and surface and shape changes are present that indicate damage does indeed occur [3537]. The findings from this study utilizing unbiased stereologic analysis highlight the need to critically evaluate the sensitivity as well as specificity of screening methods being developed to assess injury from prenatal alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%